Design and Development of Industrial Practice Monitoring and Assessment Systems using Tsukamoto Fuzzy Logic - Pahtoni, Tri Yuli; Arifin, Fatchul (Elinvo (Electronics, Informatics, and Vocational Education), 2023)
Vocational high schools are given flexibility for their students to carry out direct learning in the industry as part of the practical education activities of implementing student skills. The implementation of industrial practice requires a special way to find out and monitor each student's activities so that the achievements of the implementation of industrial practice can be carried out properly.  The implementation of industrial work practice assessment has several assessment criteria. These criteria include attendance, neatness, attitude, skills, and knowledge. The problems found in the assessment system are still done manually so that the effectiveness is minimal. This study aims to create a system that can monitor and assess the implementation of industrial practices.  The system developed will be tested as a medium for monitoring and assessing industrial practices.  This research uses Fuzzy Tsukamoto's logic approach as a scoring logic  model and  uses the waterfall method as a development model consisting of analysis, design, coding, and testing. The results of the research conducted resulted in a system that can monitor and assess the implementation of industry practices.  The test was carried out by 24 people consisting of guidance teachers and students. Testing is done by testing aspects of functionality and aspects of usability. Based on the test results, the functionality aspect scored 100% (very feasible) and the usage aspect got a score of 84.8% (very feasible)